Agricultura 4.0 na conectividade para aplicação localizada de agrotóxicos: análise econômica - Anziliero, Darlei (2022)
The digital revolution has impacted agriculture with the evolution to agriculture 4.0. Smart farms or smart farms implement the concept of integrated pest management (IPM) implementing innovation in the digital monitoring of the spatial variability of the crop using the internet of things (IoT), telemetry and big data for the collection, transfer, transformation, analysis, and application of the data in the field. There is a global increase in the use of pesticides and as the distribution of weeds, pests and diseases are not homogeneous in agricultural areas, in addition to causing productivity losses, spraying in a total area without proper monitoring and management can represent an increase in costs for the farmer. The objective of the study was to carry out a literature review in scientific articles from the main web bases between the years 2015 and 2021 and to make an economic analysis of four farms located in the Brazilian Savannah that use two 4.0 agriculture systems to monitor pests and weeds. for localized spraying of pesticides in the 2019/2020 harvest. The quantitative data of the applied area and the area where the application was saved were analyzed in an Excel spreadsheet to measure the descriptive statistics of reduction in the sprayed area, pesticide, and water savings in the spraying of first crop soybean, cotton and second crop corn, analyzing the economic viability of investments through payback, Net Present Value (NPV), Internal Rate of Return (IRR) and Benefit-Cost (B/C) calculations. The study offers benefits in understanding a new technology applied in practice in order to verify its economic performance. Analyzing the areas where it was possible to apply the technologies for localized spraying of pesticides, the distribution of pests and weeds with characteristics of spatial variability is identified. In this context, the hypotheses of the study were supported by the economic benefits of both systems, with the characteristic of heterogeneous distribution being an essential requirement for the localized application of pesticides without loss of productivity caused by damage or competition with crops. In the case of a high rate of infestation of pests and weeds in each plot, the risk of damage to the crop does not allow for the spraying to be carried out in a localized way, for this reason the application is carried out in the total area.